ASPEK DIPLOMASI, STRATEGI PERTAHANAN SEMESTA, DAN IRREGULAR WARFARE DALAM PENANGANAN GERAKAN DISINTEGRASI DI INDONESIA - Rizqa Noor Abdi; Joni Wijayanto; I Wayan Midhio (UIN Syarif Hidayatullah Jakarta, 2020)
Abstract. The aspects of diplomacy, total defense strategy, and irregular warfare are important aspects which, if combined correctly, will be effective in the strategy of winning the war, including fighting quelling uprisings that threaten the disintegration of the Unitary State of the Republic of Indonesia (Negara Kesatuan Republik Indonesia/NKRI). This paper presents a comparison of the application of the above aspects in three cases of rebellion in Indonesia, namely Darul Islam/ Tentara Islam Indonesia (DI/TII) in West Java, the Fretilin group in East Timor, and the Free Aceh Movement (Gerakan Aceh Merdeka/GAM) in Aceh. Descriptive comparisons refer to the use of library materials to describe the common thread of differences and similarities of the three movements. As a result, exposure to differences and similarities from the application of aspects of diplomacy, total defense strategy, and irregular warfare in the three cases above. Even though the time constraints and understanding of descriptive analysis may have been a limitation in this paper, the comparative presentation presented can be subject to further study, especially regarding the case of war to quell the rebellion in Indonesia. Abstrak. Aspek diplomasi, strategi pertahanan semesta, dan irregular warfare adalah aspek penting jika dikombinasikan secara tepat akan efektif dalam strategi memenangkan peperangan, termasuk perang meredam pemberontakan yang mengancam disintegrasi Negara Kesatuan Republik Indonesia (NKRI). Makalah ini memaparkan perbandingan penerapan ketika aspek di atas dalam tiga kasus pemberontakan di Indonesia, yaitu Darul Islam/Tentra Islam Indonesia (DI/TII) di Jawa Barat, kelompok Fretelin di Timor-Timur, dan Gerakan Aceh Merdeka (GAM) di Aceh. Perbandingan deskriptif mengacu kepada penggunaan bahan pustaka dilakukan untuk memaparkan benang merah perbedaan dan persamaan dari ketiganya. Hasilnya, paparan perbedaan dan persamaan dari penerapan aspek diplomasi, strategi pertahanan semesta, dan irreguler warfare dari ketiga kasus di atas. Meskipun dengan keterbatasan waktu dan pemahaman analisis deskriptif mungkin menjadi batasan dalam makalah ini, tetapi paparan perbandingan yang disampaikan dapat menjadi bahan kajian selanjutnya, khususnya menyangkut kasus perang meredam pemberontakan di Indonesia.